An analysis on thematic progression of “World Heritage Ujung Kulon National Park” by UNESCO - Aziz Nala Ardhi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
Thematic progression is when the meaning of the last theme or rheme is carried over into the next theme or rheme. Also goes into more detail about how themes can change either by